2004
DOI: 10.1111/j.1582-4934.2004.tb00319.x
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of endothelial progenitor cells in tumor angiogenesis

Abstract: Endothelial progenitor cells (EPCs) have been isolated from peripheral blood CD34, VEGFR-2, or AC 133 (CD133) antigen-positive cells, which may home to site of neovascularization and differentiate into endothelial cells in situ. Endothelial cells contribute to tumor angiogenesis, and can originate from sprouting or co-option of neighbouring pre-existing vessels. Emerging evidence indicate that bone marrow-derived circulating EPCs can contribute to tumor angiogenesis and growth of certain tumors. This review ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
97
0
15

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 49 publications
0
97
0
15
Order By: Relevance
“…They can participate in vasculogenesis in ischemic tissues, as well as in the maintenance of vascular homeostasis (Khakoo and Finkel, 2005). Emerging evidence indicate that bone marrow-derived circulating EPC can contribute to tumor angiogenesis and growth of certain tumors (Ribatti, 2004). A higher number of EPC has been demonstrated in the bone marrow of patients with active MM than in those with treated MM or with MGUS or in subjects with normal marrow (Dominici et al, 2001), which reflects the increased angiogenic potential in MM.…”
Section: Endothelial Cells Progenitor Cellsmentioning
confidence: 99%
“…They can participate in vasculogenesis in ischemic tissues, as well as in the maintenance of vascular homeostasis (Khakoo and Finkel, 2005). Emerging evidence indicate that bone marrow-derived circulating EPC can contribute to tumor angiogenesis and growth of certain tumors (Ribatti, 2004). A higher number of EPC has been demonstrated in the bone marrow of patients with active MM than in those with treated MM or with MGUS or in subjects with normal marrow (Dominici et al, 2001), which reflects the increased angiogenic potential in MM.…”
Section: Endothelial Cells Progenitor Cellsmentioning
confidence: 99%
“…An increase of circulating endothelial cells (CEC) is described in several pathologic conditions that involve vascular injury or instability as myocardial infarction, infectious vasculitis and cancer (Mutin et al, 1999;Mancuso et al, 2001;Woywodt et al, 2003;Beerepoot et al, 2004). These CEC are mostly viable and exhibit still proliferative capacity despite their terminal differentiation (Lin et al, 2000;Mancuso et al, 2001;Ribatti, 2004).…”
mentioning
confidence: 99%
“…17 It is also expressed by CD341, VEGFR-21 endothelial precursor cells, which may home to sites of neovascularization, where they differentiate into endothelial cells and contribute to tumor angiogenesis. 18 Thus, CD133 expression seems also to be linked to angiogenesis.However, data regarding the nature of these brain tumor-initiating cells are diverging, and experimental studies have identified nestin-expressing cells as the cell population susceptible to transforming events in the CNS, 19 while stem cell assays conducted on brain tumor tissue reliably produce nestin expressing tumor spheres. 11 Moreover, tumors within the same histological group often contain subgroups with different gene expression profiles that predispose the patients to clinically different outcomes.…”
mentioning
confidence: 99%
“…17 It is also expressed by CD341, VEGFR-21 endothelial precursor cells, which may home to sites of neovascularization, where they differentiate into endothelial cells and contribute to tumor angiogenesis. 18 Thus, CD133 expression seems also to be linked to angiogenesis.…”
mentioning
confidence: 99%